Review on Solar Space Heating - Cooling in Libyan Residential Buildings - Ibrahim H. Tawil (Solar Energy and Sustainable Development, 2018)
This review paper focuses on documenting and studying published papers and works in the field of solar heating and cooling air space in residential buildings. The goal of this survey and documentation is to find out the most important flushing results and conclusions specifically in fields of using solar energy for space heating, cooling and ventilation of local residential buildings in Libya. This covers using active and passive solar systems in, achieving thermal human comfort in such buildings leading to reduce electrical energy consumption. This paper also concentrates on applying energy efficiency measures in buildings; planning, design, and construction stages with the use of the principles of energy conservation in buildings. There are several studies comparing traditional with modern house designs in several local cities including both famous old cities of “Ghadames” and “Gharyan”. Several conclusions and recommendations are summarized within the text of this paper.